2018
DOI: 10.1101/490748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-OMIC analysis of brain and serum from chronically-stressed mice reveals network disruptions in purine metabolism, fatty acid beta-oxidation, and antioxidant activity that are reversed by antidepressant treatment

Abstract: Major depressive disorder (MDD) is a complex condition with unclear pathophysiology.Molecular disruptions within the periphery and limbic brain regions contribute to depression symptomatology. Here, we utilized a mouse chronic stress model of MDD and performed metabolomic, lipidomic, and proteomic profiling on serum plus several brain regions (ventral hippocampus, nucleus accumbens, and prefrontal cortex) of susceptible, resilient, and unstressed control mice. Proteomic analysis identified three serum proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…Then, the computation of the number of genome-wide stress-responsive genes, including mitochondria-associated ones, pointed at a higher reactivity of the PFC to stress than the NAc. This observation is in line with other reports showing that, at the transcriptional level, the PFC is more severely affected than the NAc by chronic stress or major depression 20 , 24 , 46 . Rodent studies have reported opposite effects of chronic stress in neuronal structure in these two brain regions, frequently indicating decreases in spine density and dendritic complexity in the PFC 47 50 while increase in the NAc 49 , 51 (but see 52 ).…”
Section: Discussionsupporting
confidence: 93%
“…Then, the computation of the number of genome-wide stress-responsive genes, including mitochondria-associated ones, pointed at a higher reactivity of the PFC to stress than the NAc. This observation is in line with other reports showing that, at the transcriptional level, the PFC is more severely affected than the NAc by chronic stress or major depression 20 , 24 , 46 . Rodent studies have reported opposite effects of chronic stress in neuronal structure in these two brain regions, frequently indicating decreases in spine density and dendritic complexity in the PFC 47 50 while increase in the NAc 49 , 51 (but see 52 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to changes in glucose/insulin metabolic pathways, we found marked differences in lipid metabolism in the hippocampus of the SR mouse lines (Figure 6d), which are consistent with recent studies showing altered lipid metabolism in depressed patients (Gowey et al, 2019;Wei et al, 2020) as well as chronic stress rodent models of MD (Hamilton et al, 2018;Oliveira et al, 2016;Patel et al, 2019). In particular, we found that, compared to both IR and LR mice, HR mice showed a significantly decreased mRNA expression of the receptor for the adipocyte-derived hormone leptin (Lepr), which is well-known to regulate calorie intake, glucose metabolism and energy expenditure (Timper & Brüning, 2017) as well as stress adaptation, possibly via the HPA axis (Roubos et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, it is recognized that lipid metabolism, in particular phospholipid and sphingolipid metabolism, is altered in psychiatric disorders, and may contribute to the etiology of these diseases. For instance, in MDD increased lipid peroxidation, derived from increased oxidative stress, as well as an inflammatory state, can induce changes in the lipid profile of the brain and in lipid metabolism, but also in lipids involved in signaling [22][23][24]. MDD treatment is also accompanied by changes in lipid metabolism [14,15].…”
Section: Introductionmentioning
confidence: 99%